Sustainable Economic Development Strategy; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Rozhdestvenskaya E. M. Elena Mikhailovna (2018, 2018)
Title screen